Transformasi digital dalam manajemen strategi perbankan - Asyhri, Ilma Ma’rifatus Zuhro (Maliki Interdisciplinary Journal, 2024)
Digital transformation has become one of the main drivers in changing the strategic management landscape of Islamic banking. This article discusses how the application of digital technology, such as artificial intelligence, data analytics, and digital platforms, can improve operational efficiency, customer experience, and product innovation in Islamic banking. Through a qualitative approach and case studies, this research explores various digital initiatives that have been adopted by Islamic banks in Indonesia and their impact on their business strategies. The findings show that digital transformation not only increases the competitiveness of Islamic banks, but also strengthens the sharia principles that form the basis of their operations. It is hoped that this article will provide insight for practitioners and academics regarding the importance of technology integration in sharia banking strategic management to achieve sustainability and growth goals in the digital era.